2019
DOI: 10.3390/rs11202415
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Below-Water Fluvial Geomorphic Change: The Implications of Refraction Correction, Water Surface Elevations, and Spatially Variable Error

Abstract: Much of the geomorphic work of rivers occurs underwater. As a result, high resolutionquantification of geomorphic change in these submerged areas is important. Currently, to quantify thischange, multiple methods are required to get high resolution data for both the exposed and submergedareas. Remote sensing methods are often limited to the exposed areas due to the challenges imposedby the water, and those remote sensing methods for below the water surface require the collection ofextensive calibration data in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 71 publications
1
25
0
Order By: Relevance
“…Other factors can also affect the development of any photogrammetric products, such as specific atmospheric conditions affecting the quality of the photo radiometry [16]; blurs appearing on the images [17]; water surface reflections [18]; and sea state, sunglint, and solar elevation angles [19]. In [20], refraction issues are additionally raised. It is claimed that using the SfM approach for submerged areas faces additional challenges, posed by the presence of water and, in particular, the effects of refraction.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors can also affect the development of any photogrammetric products, such as specific atmospheric conditions affecting the quality of the photo radiometry [16]; blurs appearing on the images [17]; water surface reflections [18]; and sea state, sunglint, and solar elevation angles [19]. In [20], refraction issues are additionally raised. It is claimed that using the SfM approach for submerged areas faces additional challenges, posed by the presence of water and, in particular, the effects of refraction.…”
Section: Introductionmentioning
confidence: 99%
“…Carrivick and Smith [16] reviewed the applications of Sf M photogrammetry and UAS technology in aquatic environments, highlighting the need of automated procedures to correct refraction. The issue of refraction correction has been addressed in several works; Woodget et al [35] quantified above and below-water geomorphic changes in a river through Sf M photogrammetry and analyzed the implications of refraction, water surface elevation and the spatial variability of topographic errors. They demonstrated that it is possible to quantify submerged geomorphic changes with levels of accuracy of less than 4 cm similar to that from exposed areas without the need of calibration data and that, using nadir imagery, the results obtained after different refraction corrections are practically the same.…”
Section: Bathymetry and Submerged Topographymentioning
confidence: 99%
“…The third paper focused on remote sensing of water depth using a different, passive optical approach that has seen increasingly widespread application in river research: Structure-from-Motion (SfM) photogrammetry. Woodget et al [9] used a sUAS to acquire multiple, overlapping images from a small river in the United Kingdom for two different time periods and showed that the level of topographic accuracy achieved in submerged areas was similar to that in exposed areas, even without separate calibration data and different SfM processing methods for within the wetted channel. Importantly, these findings imply that multiple techniques are not required to map both the subaqueous channel bed and dry bar surfaces, nor are extensive in-channel survey data.…”
Section: Bathymetry (Water Depth)mentioning
confidence: 99%
“…Moreover, the selection of a refraction correction method had little impact on results derived from near-nadir imagery. Instead, Woodget et al [9] identified improved estimation of water surface elevations as the most direct means of increasing the accuracy of SfM-based bed elevation measurements. The paper also introduced a machine learning framework for producing continuous, high-resolution maps of geomorphic change that include spatially variable error estimates.…”
Section: Bathymetry (Water Depth)mentioning
confidence: 99%